EXPERIMENTAL INVESTIGATION ON DOLOMITE DISSOCIATION INTO ARAGONITE+MAGNESITE UP TO 8.5 GPA - Sato K.; Katsura T. (My University, 2001)
We carried out high-pressure and high-temperature experiments on the composition CaMg(CO3)2 to determine the equilibrium boundary of dolomite=aragonite+magnesite up to 8.5 GPa and 1200°C, using a 6–8 type multianvil high-pressure apparatus employing a quenching technique. Dolomite dissociates into aragonite and magnesite under high P–T conditions and the phase boundary of dissociation is described by a linear equation P (GPa)=1.75+0.0061T (°C). At P>6.3 GPa and T>800°C, the equilibrium boundary was established by reverse and backward experiments to grow dolomite from mixtures of CaCO3 and MgCO3 with or without dolomite, respectively. This study suggests that the equilibrium line of the dolomite=aragonite+magnesite reaction could be very useful in addition to phase transformation of quartz–coesite and graphite–diamond to constrain P–T conditions for the metamorphism of dolomite-bearing ultrahigh-pressure rocks.